Rethinking capital flows for emerging East Asia - Stephen Grenville (Asian Development Bank Institute (ADBI), 2012)
Since the 1980s, emerging countries have been urged to welcome foreign capital inflows. The result has often been a pattern of surges, where excessive inflows were followed by damaging "sudden stops" and reversals. This was dramatically evident in the Asian crisis of 1997 - 1998. Since that crisis, the emerging countries of East Asia have typically run current account surpluses and have accumulated substantial foreign exchange reserves. This has kept them largely protected from the impact of volatile capital flows, but this strategy is neither sustainable nor optimal. What is needed is a strategy that makes use of the potential benefits of capital "flowing downhill" (that would require these countries to run current account deficits) while at the same time protecting them from both the excessive inflows and the reversals. This strategy needs to take account not only of the fickle nature of the capital flows, but the structurally-higher profitability which is characteristic of emerging countries, which motivates the excessive inflows. This strategy would require more active management of both exchange rates and capital flows than has been the accepted "best practice&". This requires a substantial shift in the current policy mindset. The International Monetary Fund has shifted some distance on this issue, but has further to go.
Keywords: F21; F31; F32; 330; asian financial crisis; east asia; financial markets; capital flows; current account; Kapitalmobilität; Kapitalverkehrskontrolle; Wirkungsanalyse; Ostasien